Curriculum Management Based on Core Academic Values in Improving the Quality of Student Education - Maulydia Wakhidatul Azizah; Fita Mustafida; Eko Setiawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
The improvement of education quality is strongly influenced by effective curriculum management. This study aims to investigate how curriculum management based on core academic values can improve the quality of student education. The research used a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The collected data were analyzed using a qualitative data analysis method. The results indicate that curriculum management based on core academic values contributes to improving educational quality by integrating essential values, such as integrity, responsibility, critical thinking, collaboration, and excellence, into the planning, implementation, and evaluation of the curriculum. The developed curriculum not only follows national policies but is also adjusted to the school’s vision as well as the needs and characteristics of the students. By involving teachers and parents in every stage of the process, the curriculum becomes more contextual and comprehensive, which ultimately improves the quality of education